Death Registration in Nigeria : A Systematic Literature Review of its Performance and Challenges - Makinde, Olusesan Ayodeji; Odimegwu, Clifford Obby; Udoh, Mojisola O.; Adedini, Sunday A.; Akinyemi, Joshua O.; Atobatele, Akinyemi; Fadeyibi, Opeyemi; Abdulaziz-Sule, Fatima; Babalola, Stella; Orobaton, Nosakhare (Taylor and Francis, 2021)
Death registration provides an opportunity for the legal documentation of death of persons. Documentation of deaths has several implications including its use in the recovery of inheritance and insurance benefits. It is also an important input for construction of life tables which are crucial for national planning. However, the registration of deaths is poor in several countries including Nigeria. This paper describes the performance of death registration in Nigeria and factors that may affect its performance. We conducted a systematic literature review of death registration completeness in Nigeria to identify, characterize issues as well as challenges associated with realizing completeness in death registration. Only 13.5% of deaths in Nigeria were registered in 2007 which regressed to 10% in 2017. There was no data reported for Nigeria in the World Health Organization database between 2008 and 2017. The country scored less than 0.1 (out of a maximum of 1) on the Vital Statistics Performance Index. There are multiple institutions with parallel constitutional and legal responsibilities for death registration in Nigeria including the National Population Commission, National Identity Management Commission and Local Government Authorities, which may be contributing to its overall poor performance.